2018
DOI: 10.1016/j.bbr.2018.02.015
|View full text |Cite
|
Sign up to set email alerts
|

Neuroinflammation in Alzheimer’s disease: Pleiotropic roles for cytokines and neuronal pentraxins

Abstract: Neuroinflammation is a potential factor speculated to underlie Alzheimer’s disease (AD) etiopathogenesis and progression. The overwhelming focus in this area of research to date has been on the chronic upregulation of pro-inflammatory cytokines to understand how neuroinflammatory mechanisms contribute to neurodegeneration. Yet, it is important to understand the pleiotropic roles of these cytokines in modulating neuroinflammation in which they cannot be labeled as a strictly “good” or “bad” biomarker phenotype.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
33
0
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 50 publications
(35 citation statements)
references
References 176 publications
(152 reference statements)
1
33
0
1
Order By: Relevance
“…Interestingly, both Neuronal pentraxin-1 (NPTX1) and Neuronal pentraxin receptor (NPTXR) showed consistent reduction (4 and 4 out of 5 studies, respectively). These proteins have been previously implicated in AD [47]. Although NPTX1 has been primarily considered as a plasma biomarker [48], the current analysis supports its role as a reliable CSF AD biomarker.…”
Section: Proteins Consistently Reduced In Ad Csfsupporting
confidence: 54%
“…Interestingly, both Neuronal pentraxin-1 (NPTX1) and Neuronal pentraxin receptor (NPTXR) showed consistent reduction (4 and 4 out of 5 studies, respectively). These proteins have been previously implicated in AD [47]. Although NPTX1 has been primarily considered as a plasma biomarker [48], the current analysis supports its role as a reliable CSF AD biomarker.…”
Section: Proteins Consistently Reduced In Ad Csfsupporting
confidence: 54%
“…Although their functions are not well understood, it is hypothesized that chitinases are involved in pro-inflammatory and proangiogenic tissue remodeling in cancer [23,24] as well as in several neurodegenerative diseases [25][26][27][28][29][30][31][32]. CHI3L1 found in the cerebral spinal fluid (CSF) obtained from preclinical and prodromal cases of AD [33][34][35] has been suggested as a biomarker for discerning cognitively normal from mild cognitive impairment (MCI) individuals [25,36,37]. Human tissue-based studies revealed that CHI3L1 is expressed in astrocytes in close apposition to blood vessels, Aβ plaques and NFTs in AD [38].…”
Section: Introductionmentioning
confidence: 99%
“…The nervous system includes the central nervous system and the peripheral nervous system. A large number of studies have found that the occurrence of various neurological diseases is closely related to neuroinflammation, which is caused by infections, trauma, toxic metabolites, and autoimmune abnormalities (75)(76)(77). Previous research suggested that circRNAs are widely distributed in the mammalian brain, at even higher abundance than the abundance of corresponding linear transcripts (7).…”
Section: Circrnas In the Neurological Diseasesmentioning
confidence: 99%